The mitochondria chronicles of melatonin and ATP: Guardians of phase separation - Doris Loh; Russel J. Reiter (Mitochondrial Communications)
Phase separation is a thermodynamic process used by all living organisms since the origin of life to rapidly assemble and disassemble membraneless condensates in response to changes in exogenous and endogenous stress conditions. For ∼4.5 billion years, living organisms in the three major domains of life depended upon the high chemical potential of adenosine triphosphate (ATP) to harness nonequilibrium chemical reactions that govern the formation and suppression of membraneless organelles via phase separation. Melatonin enhances the unique chemistry of ATP in water, promoting the solubilization via the adenosine moiety effect, supporting the survival of early organisms in an anoxic environment. Eukaryotes, including dinoflagellates and plants, can produce melatonin in extreme levels under stress as compensation for inadequate ATP for optimal regulation of survival responses dependent upon phase separation. The production of ATP and melatonin in mitochondria enables the fine-tuning of dynamics that modulate phase separation of proteins associated with ATP production, biogenesis and degradation, membrane dynamics, gene transcription, mitophagy, unfolded protein response, and apoptosis/survival responses in mitochondria. Exogenous melatonin application enhances mitochondrial ATP production and synergy, attenuating aberrant phase separation and associated mitochondrial dysfunction and disease.